Reutilización de residuos de ladrillos provenientes de construcción de edificaciones en la ciudad de Riobamba, en la elaboración de mortero de enlucidos para reducir las patologías de humedad. - Villagomez Vacacela, José Alberto (2025)
The present degree Project, entitled “Reuse of brick waste from building construction in the city of Riobamba for the production of rendering mortar to reduce moisture pathologies” addresses two significante issues: the high generation of brick waste from Construction activities and the occurrence of moisture – related pathologies in buildings. This study proposes an innovative approach to utilizing crushed brick as a partial substitute for cement in rendering mortars, there by enhancing their performance in the presence of moisture. The general objective was to develop a mortar incorporating crushed brick obtained from construction debris in Riobamba. A quantitative methodology with an experimental design was applied. Bricks were collected from five active construction sites, processed, and used to manufacture conventional and modified mortar specimens, in which 20% of the cement was replaced with crushed brick. Laboratory and field tests were conducted, including evaluations of compressive strength, sorptivity, and weathering resistance. The results indicated that the modified mortar exhibited superior mechanical performance, achieving 7.24 MPa at 28 days compared to 4.90 MPa in conventional mortar. Furthermore, it significantly reduced initial and secondary capillary water absorption. Weathering tests, which involved subjecting the mortars to simulated weather conditions for a period of (specific duration), confirmed improved durability in the modified mortars. It was concluded that incorporating crushed brick enhances the physical and mechanical properties of rendering mortars, effectively reduces moisture – related pathologies, and represents a sustainable alternative for managing construction waste in the city of Riobamba. This research provides practical insights for the construction industry and sustainability advocates.